Analisis Model Perencanaan Jalan Usaha Tani Subak Latu Terhadap Perkembangan Infrastruktur Ekowisata: Studi Jalan Usaha Tani Subak Latu Desa Abiansemal Kabupaten Badung - Ni Putu Indra Maritin; I Wayan Parwata; Agus Kurniawan (Jurnal Indonesia Sosial Teknologi, 2023)
This study aims to design a potential Subak Latu farm road design model for Abiansemal Village and analyze the perspective of acceptance and contribution of the Subak Latu farm road as an ecotourism support infrastructure to residents in the Subak Latu neighborhood in Abiansemal Village. This research uses the field development trust method in conducting potential model studies and quantitative surveys to examine the community's perspective from the perspective of benefits, risks, and community acceptance of agricultural roads. The results of this study indicate that the potential of the Jalan Usaha Tani Subak Latu model is a model with a road dimension of 2 m, equipped with supporting facilities for safety lights, guardrails, intersections, and conveniences such as seats, trash bins, and parking lots. . Furthermore, based on the results of the study, it showed that the majority of the community agreed with the construction of Jalan Usaha Tani in terms of the benefits, trust, and high public acceptance, and in terms of the low risk of Jalan Usaha Tani. This research provides a new perspective for stakeholders, related to the potential of the Jalan Usaha Tani model in collaboration with a socio-psychological approach.